Aspartic acid tagged carbon nanotubols as a tool to deliver docetaxel to breast cancer cells: Reduced hemotoxicity with improved cytotoxicity. (September 2019) - Thotakura, Nagarani; Sharma, Saurabh; Khurana, Rajneet Kaur; Babu, Penke Vijaya; Chitkara, Deepak; Kumar, Vipin; Singh, Bhupinder; Raza, Kaisar
Abstract: The present study aimed to explore the potential of hydroxylated carbon nanotubes (CNTnols) conjugated with aspartic acid for the delivery of docetaxel (DTX) to breast cancer cells. The conjugate was well-characterized by FT-IR, NMR, XRD and FE-SEM. The nanoconjugate offered a hydrodynamic diameter of 86.31 ± 1.02 nm, with a PDI of 0.113 and zeta potential of −41.6 ± 0.17 mV. The designed nanosystem offered a controlled & pH dependent release vouching release of drug in the cancerous cytosol, not in blood, assuring delivery of the pay-load to the site of action. The carriers offered substantial hemocompatibility and lower plasma protein binding, ensuring more drug available at the site of action. The in-vitro cell viability studies in MDA MB-231 cells inferred approx. 2.8 times enhancement in the cytotoxicity potential of the conjugate vis-à-vis plain drug. Pharmacokinetic studies also corroborated the superiority of the designed nanoconjugate in terms of enhanced bioavailable fractions, reduced clearance and longer bioresidence to that of plain docetaxel. The present studies, successfully provide a workable nanomedicine, loaded with a BCS class-IV drug, for improved efficacy and safety in breast cancer. Graphical abstract: Unlabelled Image Highlights: Synthesis of water soluble CNTnols and conjugation of docetaxel. Better drug loading of drug. Enhanced cytotoxicity versus plain drug. Decreased Hemo toxicity. Enhanced bioavailability in rodents.